VISUAL REPRESENTATION OF INDONESIAN LOCAL PERFUME ADVERTISEMENT IN SOCIAL MEDIA - Anisa Pratiwi; Harni Kartika Ningsih (Telkom University, 2026)
This study examines how Indonesian local perfume advertisements on Instagram construct visual meaning using Kress and van Leeuwen’s visual grammar framework. Employing a qualitative descriptive approach, the study analyzes 25 Instagram posts (53 images in total) from three Indonesian perfume brands, focusing on representational, interactional, and compositional dimensions. The findings indicate that perfume advertisements predominantly foreground the product through a combination of narrative and conceptual representations, indirect audience positioning, and visually salient composition. This study shows that visual grammar plays a key role in shaping how advertising messages are structured and interpreted within the visually driven context of Instagram.